A large and complete Jurassic geothermal field at Claudia, Deseado Massif, Santa Cruz, Argentina - Guido, Diego Martin; Campbell, Kathleen (Journal of Volcanology and Geothermal Research)
Late Jurassic geothermal deposits at Claudia, Argentinean Patagonia, are among the largest (40 km2) and most varied in the Deseado Massif, a 60,000 km2 volcanic province hosting precious metals (Au, Ag) mineralization generated during diffuse back arc spreading and opening of the South Atlantic Ocean. Both siliceous sinter and travertine occur in the same stratigraphic sequence. Deposits range from those interpreted as fluvially reworked hydrothermal silica gels, to extensive apron terraces, to a clustering of high-temperature subaerial vent mounds. Paleoenvironmentally diagnostic textures of sinters include wavy laminated, bubble mat and nodular fabrics, and for travertines comprise fossil terracette rims, wavy laminated, bubble mat, spherulitic, oncoidal, and peloidal fabrics. Of special note is the presence of relatively large (to 25 cm high), inferred subaqueous “Conophyton” structures in travertines, which serve as analogs for some Precambrian stromatolites and imply the presence of relatively deep pools maintained by voluminous spring discharges. The Claudia geothermal field is geographically and geologically linked to the Cerro Vanguardia epithermal project (total resource of ~ 7.8 million ounces Au equivalent) via proximity, similar veins, and structural linkages, making it an especially large and relevant prospect for the region. The combined Claudia–Cerro Vanguardia hydrothermal system likely represents a fortuitous alignment of focused fluid flow and structure conducive to forming a giant epithermal ore deposit, with respect to size, ore concentration and potentially duration, in the Late Jurassic of Patagonia. Fil: Guido, Diego Martin. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Instituto de Recursos Minerales. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas. Instituto de Recursos Minerales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Campbell, Kathleen. The University Of Auckland; Nueva Zelanda